THE ROLES OF ESP TEACHERS’ KNOWLEDGE OF THEIR STUDENTS' ACADEMIC SUBJECTS - Kusni, Kusni (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This paper describes the roles of ESP teachers’ knowledge of their students’ particular academic subjects. This topic is a reflection of a small part of two surveys done along 2002-2003 and 2007 at universities: University of Indonesia, Padjadjaran University, and Andalas Unversity, State University of Padang, Bung Hatta University, and Eka Sakti University. Both surveys involved total parties of respondents: 590 students, 23 ESP teachers, 18 heads of department, 18 senior lecturers of the departments being surveyed, and 10 TEFL specialists. The findings of the research reflected that the ESP teachers should have basic knowledge of their students’ academic subject.